The Burden of Illness Related to Chronic Obstructive Pulmonary Disease Exacerbations in Québec, Canada - Tam Dang-Tan; Shiyuan Zhang; Ruben V. Tavares; Melissa Stutz; Afisi S. Ismaila; Julie Vaillancourt; Diane Corriveau; Richard H. Stanford; Xiwu Lin; Gilbert A. Nadeau; Alexander Simidchiev; Daria Parsons; et al. (Canadian Respiratory Journal)
Background. Chronic obstructive pulmonary disease (COPD) prevalence in Canada has risen over time. COPD-related exacerbations contribute to the increased health care utilization (HCU) in this population. This study investigated the impact of exacerbations on COPD-related HCU. Methods. This retrospective observational cohort study used patient data from the Québec provincial health insurance databases. Eligible patients with a new HCU claim with a diagnostic billing for COPD during 2001–2010 were followed until March 31, 2011. Exacerbation rates and time to first exacerbation were assessed. Unadjusted analyses and multivariable models compared the rate of HCU by exacerbation classification (any [moderate/severe], moderate, or severe). Results. The exacerbation event rate in patients with an exacerbation was 34.3 events/100 patient-years (22.7 for moderate exacerbations and 11.6 for severe exacerbations). Median time to first exacerbation of any classification was 37 months. In unadjusted analyses, COPD-related HCU significantly increased with exacerbation severity. In the multivariable, HCU rates were significantly higher after exacerbation versus before exacerbation (p<0.01) for patients with an exacerbation or moderate exacerbations. For severe exacerbations, general practitioner, respiratory specialist, emergency room, and hospital visits were significantly higher after exacerbation versus before exacerbation (p<0.001). Conclusions. Exacerbations were associated with increased HCU, which was more pronounced for patients with severe exacerbations. Interventions to reduce the risk of exacerbations in patients with COPD may reduce disease burden.